Pharmacokinetic and pharmacodynamic properties of orally administered torasemide in healthy cats. (30th July 2022) - Roche‐Catholy, Marine; Paepe, Dominique; Devreese, Mathias; Broeckx, Bart J. G.; Woehrlé, Frederique; Schneider, Marc; de Salazar Alcala, Andrea Garcia; Hellemans, Arnaut; Smets, Pascale
Abstract: Background: In people and dogs, torasemide has higher bioavailability, longer half‐life, and longer duration of action than equivalent doses of furosemide but data regarding pharmacological properties of torasemide in cats are limited. Objective: To assess pharmacokinetic and pharmacodynamic parameters of torasemide in healthy cats, and to investigate the effects of a single administration of torasemide on indicators of diuresis, plasma creatinine concentration, blood pressure, electrolyte concentrations and markers of the renin‐angiotensin‐aldosterone system (RAAS). Animals: Six clinically healthy adult European shorthair cats. Methods: Randomized 4‐period crossover design with 3 groups and 4 treatments. Pharmacokinetic parameters were obtained using a noncompartmental analysis, and the clinically effective dose was assessed using a Hill model. Results: Mean absolute bioavailability was estimated at 88.1%. Mean total body clearance was 3.64 mL/h/kg and mean terminal half‐life was 12.9 hours. Urine output significantly increased after torasemide administration ( P  < .001). The urine sodium : potassium ratio (uNa : uK) paralleled and was statistically correlated to urine output ( P  < .001). Administration of a single torasemide dose led to a significant dose‐dependent increase in urine aldosterone : creatinine ratio (uAldo : C; P  < .001) and a transient decrease in plasma potassium concentration ( P  < .001) but did not affect blood pressure or plasma creatinine concentration. Conclusions and Clinical Importance: A single torasemide dose leads to a significant increase in diuresis and renin‐angiotensin‐aldosterone system (RAAS) activation in healthy cats, with high absolute bioavailability, and without clinically relevant adverse effects. Pharmacokinetic parameters indicate that once daily dosing of 0.27 mg/kg may be appropriate in a clinical setting.